Transjugular intrahepatic portosystemic shunt for hepatorenal syndrome: A systematic review and meta-analysis. Issue 4 (April 2018) - Song, Tingxue; Rössle, Martin; He, Fuliang; Liu, Fuquan; Guo, Xiaozhong; Qi, Xingshun
Abstract: Background: Hepatorenal syndrome is a severe complication of advanced liver diseases with a dismal prognosis. Aims: This systematic review and meta-analysis aims to explore the efficacy and safety of transjugular intrahepatic portosystemic shunt for the treatment of hepatorenal syndrome. Method: Publications were searched via PubMed and EMBASE databases. The pooled proportion and mean difference were calculated by using a random-effect model. Results: Nine publications were included, in which 128 patients with hepatorenal syndrome were treated with transjugular intrahepatic portosystemic shunt. The pooled short-term and 1-year survival rates were 72% and 47% in type 1 hepatorenal syndrome and 86% and 64% in type 2 hepatorenal syndrome. No lethal procedure-related complications were observed. The pooled rate of hepatic encephalopathy after transjugular intrahepatic portosystemic shunt was 49%. The pooled rate of renal function improvement after transjugular intrahepatic portosystemic shunt was 93% in type 1 hepatorenal syndrome and 83% in any type of hepatorenal syndrome. After transjugular intrahepatic portosystemic shunt, serum creatinine, blood urea nitrogen, serum sodium, sodium excretion, and urine volume were significantly improved; by comparison, serum bilirubin slightly increased, but the difference was not statistically significant. Conclusion: Limited evidence suggested a potential survival benefit of transjugular intrahepatic portosystemic shunt in patients with hepatorenal syndrome but with a high incidence of hepatic encephalopathy.